An Ecological Approach to Selected Turkish Folk Tales - Senocak, Ebru; Kocsoy, F. Gul (Rector Ciu Cyprus Int Univ, 2024)
In this article, we investigate selected Turkish animal tales that include ecological sensitivity and consciousness. From an ecological perspective, all living and nonliving creatures, including human beings, are connected to one another like a chain, and each one is equal. Unlike the anthropocentric point of view, which sees humans as the rulers of the universe, ecocentrism regards every being as having equal importance, value, and place in the universe. It does not give any extra privileges to humans. In ecocentric thought, every being is in close relationship with others and affects them. These beings' actions and words influence one another. Folk tales, as extensions of myths and products of the collective unconscious, enable the discovery of nature's beauties, its unknown or unrecognized secrets, and address issues of creation and cosmogony. Folk tales, which encode the awareness of protecting nature and environmental consciousness in symbols, invite human beings to be conscious and responsible towards nature. Many tales, which also contain important messages regarding environmental ethics, guide the reader on a journey of maturation and help lay the foundations for a healthy, balanced, and conscious future. In these tales, one wrong done to another affects all the other beings in the system, and its effects are difficult to compensate for. Conversely, acts of goodness are profusely rewarded and lead to peace and balance, not only within the community but also within the characters' inner lives. Rejecting anthropocentrism, the eco-centered attitude defends and prioritizes nature's wellbeing. The tales offer numerous teachings for humanity. The ecocentric stance in these tales prescribes that humans should learn from the workings, harmony, and elements of nature. They reveal the advantages of goodness and virtue while exhibiting the disadvantages brought about by wickedness. They emphasize that nature possesses wisdom, and if humanity conforms to its wisdom and order, it will lead a life of pleasure. Rebirth is possible when a member of nature harms its elements or rhythm but later becomes repentant and remedies the harm. In this article, using the methods of eco-criticism, these points are analyzed and illustrated.
Seçilmiş Türk Halk Masallarına Ekolojik Bir Yaklaşım
Keywords: Turkish folk tales; ecological consciousness; ecocentrism; eco-criticism